Studi Riview : Media Pembelajaran Biologi Dalam Meningkatkan Motivasi Belajar Siswa Terhadap Kesadaran Lingkungan Sekitar - Revi Ruth Susanty; Putri Nora; Marina Azzahra Nasution; Aryediatami Naura Kamila; Ashar Hasairin (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
This literature study aims to find out and analyze the role of various learning media in increasing student learning motivation towards environmental awareness. This study uses a literature review method, namely by collecting research articles found in Pubmed and Google Scholar from 2019-2024 using the keywords "the influence of learning media on increasing student motivation towards environmental awareness". Based on the results of the literature review, it can be concluded that learning media that can increase students' learning motivation are animated video media based on environmental issues, animated video media based on green schools, digital infographic media, virtual reality media, powtoon media, and edpuzzle media.